Magnetic and superconducting properties of FeSe1–xTex (x ≃ 0, 0.5, and 1.0): Сверхпроводимость - Fedorchenko, A.V.; Volkova, O.S.; Chareev, D.A.; Loidl, A.; Nidda, H.-A. Krug von; Deisenhofer, J.; Tsurkan, V.V.; Gnatchenko, S.L.; Panfilov, A.S.; Desnenko, V.A.; Grechnev, G.E.; Vasiliev, A.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
Magnetization studies for FeSe1–xTex (x ≃ 0, 0.5, and 1.0) compounds were carried out in magnetic fields up to 50 kOe and in the temperature range 2–300 K. The superconducting transition was observed at Tc ≃ 8 K and 13.6–14.2 K in FeSe0.963 and FeSe0.5Te0.5, respectively. For the most samples, a nonlinear behavior of the magnetization curves in the normal state gives evidence of a commonly observed substantial presence of ferromagnetic impurities in the compounds under study. By taking these impurity effects into account, the intrinsic magnetic susceptibility χ of FeSe0.963, FeSe0.5Te0.5, and FeTe was estimated to increase gradually with Te content. For FeTe a drastic drop in χ(T) with decreasing temperature was found at TN ≃ 70 K, which is presumably related to antiferromagnetic ordering. To shed light on the observed magnetic properties, ab initio calculations of the exchange enhanced magnetic susceptibility are performed for FeSe and FeTe within the local spin densityapproximation.